2020
DOI: 10.1002/bjs5.50257
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized intraperitoneal aerosol chemotherapy: a review of the introduction of a new surgical technology using the IDEAL framework

Abstract: Background The IDEAL (Idea, Development, Evaluation, Assessment, Long‐term study) framework is a scheme of investigation for innovative surgical therapeutic interventions. Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is a procedure based on laparoscopy to deliver intraperitoneal chemotherapy for peritoneal metastases, introduced in 2011. The aim of this article was to review literature on PIPAC and assess whether development of the technique has followed the IDEAL framework. Methods A search of MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…Five other studies have performed a systematic review of clinical studies on PIPAC for the treatment of peritoneal metastases (10,(41)(42)(43)(44). However, none of these systematic reviews specifically focused on PIPAC-OX in patients with CPM alone and reported on the interpretability of the results of included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Five other studies have performed a systematic review of clinical studies on PIPAC for the treatment of peritoneal metastases (10,(41)(42)(43)(44). However, none of these systematic reviews specifically focused on PIPAC-OX in patients with CPM alone and reported on the interpretability of the results of included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing and future trials have to clarify the role of this therapeutic concept in these settings [27]. Current and future challenges for PIPAC has recently been surveyed [28,29]. The dose of oxaliplatin currently applied during PIPAC was determined arbitrarily and copied the drug concentration in the aerosol as practiced in the HIPEC perfusate [30].…”
Section: Discussionmentioning
confidence: 99%
“…PIPAC has the advantage of a higher pressure that does not exceed tumor interstitial pressure. However, it seems important to underline that the majority of the studies investigating this procedure since its introduction in 2011 have not encompassed the IDEAL (Idea, Development, Evaluation, Assessment, Long-term study, Framework) framework [ 38 ]. The PIPAC procedure was meticulously tested in a porcine model and compared to washing techniques.…”
Section: Methods Of Deliverymentioning
confidence: 99%